2022
DOI: 10.1051/0004-6361/202141897
|View full text |Cite
|
Sign up to set email alerts
|

Ambilateral collimation study of the twin-jets in NGC 1052

Abstract: Context. With the increase in the sensitivity and resolution of radio interferometry within recent years, the study of the collimation and acceleration region of extragalactic jets in active galactic nuclei (AGN) has come into focus. Whereas a large fraction of AGN jets show a change from parabolic to conical collimation profile around the Bondi radius, there is a small number of sources that display a deviation from this standard picture, including the radio galaxy NGC 1052. Aims. We study the jet width profi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
3
9
0
Order By: Relevance
“…All distances are expressed with respect to the 43 GHz core, assumed to coincide with the actual position of the black hole. This assumption is supported by previous observational results, showing that the mm-core in radio galaxies lies very close (< 100𝑅 S ) to the true position of the central black hole (e.g., Hada et al 2011;Baczko et al 2022).…”
Section: Data Set and Image Analysissupporting
confidence: 83%
“…All distances are expressed with respect to the 43 GHz core, assumed to coincide with the actual position of the black hole. This assumption is supported by previous observational results, showing that the mm-core in radio galaxies lies very close (< 100𝑅 S ) to the true position of the central black hole (e.g., Hada et al 2011;Baczko et al 2022).…”
Section: Data Set and Image Analysissupporting
confidence: 83%
“…In the case of M87, Asada & Nakamura (2012) showed that such a geometry transition can be observed in the vicinity of the Bondi-sphere (Russell et al 2015) where the external medium is expected to change its pressure gradient. More recent works also found these transitions in several different sources, NGC 6251 (Tseng et al 2016), NGC 4261 (Nakahara et al 2018), NGC 1052 (Nakahara et al 2020;Baczko et al 2022), NGC 315 (Boccardi et al 2021;Park et al 2021) and 1H0323+342 (Hada et al 2018). In the cases of M87 (Mertens et al 2016;Hada et al 2018;Park et al 2019), NGC 315 (Park et al 2021) and 1H0323+342 (Hada et al 2018) the jets also show accelerating jet components near the geometry-transition zones.…”
Section: Introductionmentioning
confidence: 65%
“…In this study we made use of the orthogonal distance regression (ODR) as used in Baczko et al (2016), Baczko et al (2019) and Baczko et al (2022) in order to fit the smoothly broken power law in the geometry transition sources. For the discussion in this paper, we use the least square implementation in scipy with the trust-region reflective algorithm in order to fit the smoothly broken power law which allows us to set bounds on each parameter which we get from the numerical method when searching for a possible break in geometry in each jet.…”
Section: Appendix B: Comparing Different Fit Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting example is the lowionisation nuclear emission line region (LINER) galaxy NGC1052 with twin-jets. Baczko et al (2022) find that both jets are conical downstream of a break in the jet collimation profile at 10 4 R s . However upstream of the jets, the jet collimation profile is neither cylindrical nor parabolic for the approaching jet and close to cylindrical for the receding one.…”
Section: Nuclear or Vlbi-scale Jetsmentioning
confidence: 74%